Environmental perspectives of textile waste, environmental pollution and recycling. Issue 1 (31st December 2022) - Zhou, Quan; Le, Quyet Van; Meng, Lingbo; Yang, Han; Gu, Haiping; Yang, Yafeng; Chen, Xiangmeng; Lam, Su Shiung; Sonne, Christian; Peng, Wanxi
ABSTRACT: The environmental concerns caused by textile waste require technological development to support recycling and re-utilization. Incineration and landfill of textile waste are still widely used, and they lead to soil and water pollution as well as emissions of greenhouse gases. Recently, various research studies on textile waste treatment try to find appropriate technical means to realize environmental protection and sustainable recycling. Here, we summarize and discuss new ways to improve the treatment of textile waste, including its utilization value and transformation ways, to help remediation and lower environmental impacts. This paper comprehensively expounds on the current situation of textile waste treatment and the recycling value of different types of textile waste. This includes recycling composite materials, fillers, energy materials and carbonized adsorption material, which support sustainable development with social and economic benefits. Overall, this shows that textile waste needs to be separated at large scales globally to reduce the carbon footprint, improve socio-economic benefits and mitigate environmental pollution. Otherwise, there is a risk that the global warming and ecosystem transformations, due to pollution and urbanization, could lead to severe adverse effects such as cancer and global pandemics. GRAPHICAL ABSTRACT: UF0001